Oral Health status of 3-6 year old children and their mother’s oral health related knowledge, attitude and practices in Mysore City, India - Bennadi, Darshana; Reddy, C. V.K.; Sunitha, S.; Kshetrimayum, Nandita (Asian Journal of Medical Sciences, 2014)
Aims and Objectives: The study was carried out to assess oral health status of 3-6 year old children and their mother’s oral health related knowledge, attitude and practices in Mysore city. Moreover, this study also carried out to determine whether mother’s oral health related knowledge, attitude and practices influences oral health of their children. Materials and Methods: A total of 500 children belonging to the age group of 3-6 years old attending both governments sponsored and private preschools from five sectors accompanied by their mothers formed the study group. Oral health status was assessed by using decayed missing filled teeth index (dmft) and plaque index. Mother’s knowledge, attitude and practices were assessed by direct contact with mothers using closed ended questionnaire. Results: The results of the study showed that the prevalence of dental caries among children was 64% with mean dmft of 3.20 ± 3.08 and mean plaque scores was 0.87 ± 0.33. There was significant correlation between plaque scores and dmft. dmft and plaque score was higher in older individuals and the difference was highly significant. Mean plaque score was more among the government preschool children (1.02 ± 0.31). 46% of mothers had medium level knowledge, 63.2% mothers had average attitude and 51% mothers had high level practices related to oral health. An inverse relationship was found between mean dmft, caries prevalence, mean plaque score in children and mother’s knowledge, attitude and practices about oral health and the findings were highly significant. Conclusion: Results showed that mother’s oral health related knowledge; attitude and practices had influence on oral health status of their children DOI: http://dx.doi.org/10.3126/ajms.v6i2.11097 Asian Journal of Medical Sciences Vol.6(2) 2015 66-71